Source codeVideos

Command Palette

Search for a command to run...

Understanding Inverse Functions

You often translate words or sentences from English to Indonesian, for example, when watching movies or reading news. This translation process is similar to how a function works: there is an input (English word) and an output (Indonesian word).

Consider the following illustration:

Translation Machine
The translation machine changes words or sentences from English to Indonesian.
Translation Machine

Here, the "Translation Machine" acts like a function that transforms "Mathematics" (input) into "Matematika" (output).

Now, what if we want to do the reverse? Translate "Matematika" back into "Mathematics"?

This reverse process is the basis of the inverse function concept.

Definition of Inverse Function

An inverse function is a function that "reverses" the operation of an initial function. If function ff maps element xx from domain AA to element yy in codomain BB, then its inverse function, denoted as f1f^{-1} (read "f inverse"), maps element yy from BB back to element xx in AA.

Mathematically:

y=f(x)    x=f1(y)y = f(x) \iff x = f^{-1}(y)

In other words, if ff changes xx to yy, then f1f^{-1} changes yy back to xx. The inverse function "undoes" the effect of the original function.

Important: The notation f1(x)f^{-1}(x) does not mean 1f(x)\frac{1}{f(x)} (multiplicative inverse or reciprocal). It is special notation for the inverse function.

Condition for a Function to Have an Inverse

Not all functions have an inverse function. For a function ff to have an inverse function f1f^{-1}, the function ff must be bijective. A bijective function is both injective (one-to-one) and surjective (onto).

  • Injective (One-to-one): Every distinct element in the domain maps to a distinct element in the codomain. No two different inputs produce the same output.
  • Surjective (Onto): Every element in the codomain is the result of mapping from at least one element in the domain. All possible outputs occur.

If function ff is not bijective, its inverse relation might exist, but that relation will not be a function.

Determining the Formula for an Inverse Function

To find the formula for the inverse function f1(x)f^{-1}(x) from a function f(x)f(x), you can follow these steps:

  1. Replace f(x)f(x) with yy.
  2. Swap the positions of the variables xx and yy in the equation.
  3. Solve the equation for yy in terms of xx.
  4. Replace yy with f1(x)f^{-1}(x) to get the inverse function formula.

Example:

Find the inverse function of f(x)=2x+3f(x) = 2x + 3.

  1. Replace f(x)f(x) with yy:

    y=2x+3y = 2x + 3
  2. Swap xx and yy:

    x=2y+3x = 2y + 3
  3. Solve for yy:

    x3=2yx - 3 = 2y
    x32=y\frac{x - 3}{2} = y
  4. Replace yy with f1(x)f^{-1}(x):

    f1(x)=x32f^{-1}(x) = \frac{x - 3}{2}

So, the inverse function of f(x)=2x+3f(x) = 2x + 3 is f1(x)=x32f^{-1}(x) = \frac{x - 3}{2}.

Graph of a Function and Its Inverse

The graph of the inverse function f1(x)f^{-1}(x) is a reflection of the graph of the original function f(x)f(x) across the line y=xy = x.

For example, let's look at the graph of f(x)=2x+3f(x) = 2x + 3, its inverse f1(x)=x32f^{-1}(x) = \frac{x - 3}{2}, and the identity line y=xy=x.

Graph of f(x)f(x) and its Inverse
The graph shows the function f(x)f(x), its inverse f1(x)f^{-1}(x), and the line y=xy=x as the line of reflection.